2011
DOI: 10.1007/s13595-011-0125-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thinning intensity on radial growth patterns and temperature sensitivity in Pinus canariensis afforestations on Tenerife Island, Spain

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
3
29
0
1
Order By: Relevance
“…1). This result was in accordance with previous studies which reported poor individual growth responses after light thinning in comparison to heavy thinning (Martín-Benito et al 2010;Perez-de-Lis et al 2011). Furthermore we found the distinct effects of GT on the earlywood and latewood growth (Table 2; Fig.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…1). This result was in accordance with previous studies which reported poor individual growth responses after light thinning in comparison to heavy thinning (Martín-Benito et al 2010;Perez-de-Lis et al 2011). Furthermore we found the distinct effects of GT on the earlywood and latewood growth (Table 2; Fig.…”
Section: Discussionsupporting
confidence: 94%
“…Whereas intermediate trees inhabited the middle canopy position and still competed for light and other resources with dominant trees on the closed-forest sides of their canopies. Therefore, their growth might be still limited after gap creation (Jones and Thomas 2004;Perez-de-Lis et al 2011). The weak correlations between radial growth of suppressed trees and microclimate variables suggested that the microclimate condition had only little influence on growth of suppressed trees (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, thinning is, generally, performed with the aim of accelerating secondary succession and increasing the overall biodiversity, enhancing the heterogeneity and structural diversity of the forest stand and improving the status of the remaining trees [7,13,52]. Different thinning intensities are usually required for different forest types and species [52,53].…”
Section: Pine Management and Thinningmentioning
confidence: 99%
“…The tree growth answer to thinning is according to its intensity [128]. At Scots Pine, it was found that the thinnings stimulate the division of cambium [39].…”
Section: Trees Response To Managementmentioning
confidence: 99%